Contesting Flexible Solidarity: Poland and the “Migration Crisis” - Goździak, Elżbieta M.; Main, Izabella (Frontiers in Human Dynamics, 2020)
New forms of solidarity are being shaped as a response to the European “refugee crisis. ” The states have not been able to implement any viable or sustainable solution to the crisis, but the solidarity movement has been very visible and active in many European countries and rejected in others. This paper focuses on Poland, a country that gave birth to the Solidarność labor movement in 1980, but was recently reprimanded by the European Union for its lack of solidarity with other countries that accepted refugees. In this paper, we trace the rapture of the Solidarity movement and the emergence of solidarities with migrants and refugees in local Polish communities and abroad. We juxtapose the Polish government's call for “flexible solidarity” mechanisms within the EU, coupled with the emphasis on solidarity in the context of border securitization, with grassroots efforts in several Polish cities to welcome migrants and refugees and facilitate their integration. We also look at the emerging initiatives to raise resources to help refugees lingering in refugee camps and transit countries. And finally, we ask the question whether fragmented, organically evolving, grass-root solidarities are sustainable without the support of the national government.